LEGISLASI QANUN JINAYAT ACEH DALAM SISTEM HUKUM NASIONAL - Amsori, Amsori; Jailani, Jailani (UIN Ar-Raniry, 2017)
This research moved from the process and formulation mekanism of Jinayat Law into Positive Law in Aceh in Indonesia's legal system is influenced by a variety of legal systems and ideologies that developed there in. The object of this study is the Aceh Qanun No. 6 of 2014 on the law Jinayat that the legislative process takes place during two periods of provincial parliament. This study is qualitative, by combining the research literature (library reseacrh) with field research (field reseacrh). The approach used consisted of approach law (statute approach), normative-empirical approach and conceptual approaches. Type of research data in the form of descriptive analysis. The results showed the legal legislation jinayat Aceh is gradually taking into account the socio-cultural conditions of the community in accepting the substance of the law jinayah, adaptive law enforcement and crime rates are dominant in society. Parties involved in the formulation of the substance Raqan jinayah Aceh, among others: Ulama Consultative Assembly (MPU), law enforcement agencies (Syari'yyah Court, the Prosecutor, the Police and the WH) as well as the public through non-governmental organizations. The Aceh Government also involves the Expert Team Expert Team Executive and Legislature in the substance of the discussion on the draft jinayah. The dynamics of thought that emerged in the formulation of the substance of the criminal law (Jinayah) should be sought common ground in order Raqan jinayah be passed along between the legislative and the executive.